The Effect of Entry Qualifications and Gender Towards Student Performance - M. M., Noor; K., Kadirgama; M. R. M., Rejab; M. Y., Taib (2009)

(untitled)
Student entry qualifications are vital issue. This paper presents the influence of gender, entry qualification and entry results towards the student performance in university. 65 students were randomly selected in Faculty of mechanical engineering, University Malaysia Pahang. Entries qualifications are from Foundation Program, Higher Certificate of Malaysian Education (STPM) and Diploma Certificate. STPM is form six examinations in secondary school level. Genetic Algorithms (GA) and Radian Basis Function Network (RBFN) method was used to measure and predict the student’s performance. Gender not plays the major role but entry results plays important role. Good entry results student normally maintain their momentum. GA and RBFN plays important role to study the student performance with different type of variables.